Stochastic simulation of hemagglutinin-mediated fusion pore formation. - Schreiber, S (2001)
Studies on fusion between cell pairs have provided evidence that opening and subsequent dilation of a fusion pore are stochastic events. Therefore, adequate modeling of fusion pore formation requires a stochastic approach. Here we present stochastic simulations of hemagglutinin (HA)-mediated fusion pore formation between HA-expressing cells and erythrocytes based on numerical solutions of a master equation. The following elementary processes are taken into account: 1) lateral diffusion of HA-trimers and receptors, 2) aggregation of HA-trimers to immobilized clusters, 3) reversible formation of HA-receptor contacts, and 4) irreversible conversion of HA-receptor contacts into stable links between HA and the target membrane. The contact sites between fusing cells are modeled as superimposed square lattices. The model simulates well the statistical distribution of time delays measured for the various intermediates of fusion pore formation between cell-cell fusion complexes. In particular, these are the formation of small ion-permissive and subsequent lipid-permissive fusion pores detected experimentally (R. Blumenthal, D. P. Sarkar, S. Durell, D. E. Howard, and S. J., J. Cell Biol. 135:63-71). Moreover, by averaging the simulated individual stochastic time courses across a larger population of cell-cell-complexes the model also provides a reasonable description of kinetic measurements on lipid mixing in cell suspensions (T. Danieli, S. L. Pelletier, Y.I. Henis, and J. M. White, 1996, J. Cell Biol. 133:559-569).